PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA GURU PADA SEKOLAH DASAR NEGERI 009 KUALA TERUSAN KECAMATAN PANGKALAN KERINCI - Manik, Sudarmin; Syafrina, Nova (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at State Elementary School 009 Kuala Terusan Pangkalan Kerinci Subdistrict. With the aim of research to know the influence of work environment on teacher performance Elementary School 009 Kuala Terusan. Population in this research is all teacher of SDN 009 Kuala Terusan, while sampe in this research is counted 34 teacher. Data analysis used is validity test, reliability test, normality test, simple linear regression test and coefficient of determination test. While the hypothesis test using t test. Result of this research that work environment variable have positive and significant effect to teacher performance Elementary School 009 Kuala Terusan Sub Pangkalan Kerinci